2019
DOI: 10.15420/icr.2019.06.r3
|View full text |Cite
|
Sign up to set email alerts
|

Drug-coated Balloons for Small Coronary Vessel Interventions: A Literature Review

Abstract: Newer-generation drug-eluting stents (DES) are the standard of care for the treatment of symptomatic coronary artery disease. However, some lack of efficacy has been reported in small coronary arteries based on higher rates of target lesion restenosis, thrombosis and MI resulting in repeated interventions. Drug-coated balloons (DCBs) are an established treatment option for in-stent restenosis in both bare metal stents and DES and they can deliver an anti-proliferative drug into the vessel wall without implanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…In parallel with our results, Jeger et al demonstrated the same benefits of DEB versus DES for small coronary artery disease PCI in an open-label randomized noninferiority trial 31. This finding is supported by recent reports emphasizing DEB is a promising technique for certain de novo coronary lesions, with improved safety and efficacy 32. According to Hirohata et al, directional atherectomy in conjunction with DEB improves outcomes in LCx ostial stenosis and could soon be considered as a stentless therapeutic option 33.…”
supporting
confidence: 90%
“…In parallel with our results, Jeger et al demonstrated the same benefits of DEB versus DES for small coronary artery disease PCI in an open-label randomized noninferiority trial 31. This finding is supported by recent reports emphasizing DEB is a promising technique for certain de novo coronary lesions, with improved safety and efficacy 32. According to Hirohata et al, directional atherectomy in conjunction with DEB improves outcomes in LCx ostial stenosis and could soon be considered as a stentless therapeutic option 33.…”
supporting
confidence: 90%
“…In the process of PCI treatment, whether it is the injury caused by balloon expansion to the intima or the mechanical stimulation generated by the stent, it may exert an activation effect on inflammatory factors, induce local inflammation, and then stimulate smooth muscle cells [27,28]. The proliferation reaction also causes a certain deposition of extracellular matrix, resulting in thickening of the intima and ISR [29]. Some doctors [30] have pointed out that both the diameter of the blood vessel and the length of the stent have a certain correlation with the ISR.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have demonstrated the successful delivery of sirolimus into the tunica medial layer, with some drugs extending into the adventitia (19). The DCB used in this study uses a unique phospholipid coating technology to allow for 100% sirolimus submicron drug particle coating on the balloon surface to facilitate controlled drug delivery into the vessel wall when the balloon is inflated (20).…”
Section: Discussionmentioning
confidence: 99%